Features technical and tactical training of volleyball players of high class of different roles - Olha Shlonska (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the effectiveness of competitive activity of highly skilled players in different roles. Material and Methods: the study used statistical data of major international competitions: the Olympic Games - 2012, the World Cup - 2010, 2014, European Championship - 2010-2014 World League - 2010-2014. A total of 130 games was analyzed. Methods used: analysis and compilation data of special scientific and methodical literature, analysis of competitive activity of volleyball players of high class, pedagogical observation, methods of mathematical statistics. Results: it was found that the most effective of attacking actions during one game performed by highly skilled volleyball players of the world, where players first rate of the attack wins in the fourth part 4,2% balls, the second player tempo attak - 4,5%, «diagonal» - 5,1%. Conclusion: it is proved that the greatest indicator of the effectiveness of competitive activity has a high-class volleyball players that win throughout the game the second player tempo attak 22,1% of balls, «diagonal» - 18,8%, the first rate players - 16,3%